The Influence of Carbon Dioxide on Brain Activity and Metabolism in Conscious Humans - Xu, Feng; Uh, Jinsoo; Brier, Matthew R; Hart, John; Yezhuvath, Uma S; Gu, Hong; Yang, Yihong; Lu, Hanzhang (Journal of cerebral blood flow and metabolism, 2011)
A better understanding of carbon dioxide (CO2) effect on brain activity may have a profound impact on clinical studies using CO2 manipulation to assess cerebrovascular reserve and on the use of hypercapnia as a means to calibrate functional magnetic resonance imaging (fMRI) signal. This study investigates how an increase in blood CO2, via inhalation of 5% CO2, may alter brain activity in humans. Dynamic measurement of brain metabolism revealed that mild hypercapnia resulted in a suppression of cerebral metabolic rate of oxygen (CMRO2) by 13.4%±2.3% (N=14) and, furthermore, the CMRO2 change was proportional to the subject's end-tidal CO2 (Et-CO2) change. When using functional connectivity MRI (fcMRI) to assess the changes in resting-state neural activity, it was found that hypercapnia resulted in a reduction in all fcMRI indices assessed including cluster volume, cross-correlation coefficient, and amplitude of the fcMRI signal in the default-mode network (DMN). The extent of the reduction was more pronounced than similar indices obtained in visual-evoked fMRI, suggesting a selective suppression effect on resting-state neural activity. Scalp electroencephalogram (EEG) studies comparing hypercapnia with normocapnia conditions showed a relative increase in low frequency power in the EEG spectra, suggesting that the brain is entering a low arousal state on CO2 inhalation.